Effect of NPK, boron and zinc on productivity and profitability of late sown kharif maize (Zea mays L.) in western Uttar Pradesh, India - Singh, Satybhan; Singh, Virendra; Mishra, Parmanand (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif 2015 at the research farm of IFTM University,Lodhipur, Rajput, Moradabad to study the effect of NPK (100% and 120% recommended dose offertilizers), boron(10 kg B ha–1) and zinc (10 kg Zn ha–1) fertilization on growth, yield and economicsof late sown maize. The experiment was laid out in RBD replicated thrice. Growth attributes likeplant height, fresh and dry weight, yield attributes (cob length, number of grains per cob, 1000-seedweight), seed yield, stover yield, harvest index and gross returns, net returns and benefit: cost ratio;were to be enhanced significantly by the application of 120% recommended dose of fertilizer (RDF)over 100% RDF. Addition of boron @10 kg ha–1 and zinc @10 kg ha–1 had marked effect on allgrowth and yield characters, yield, gross returns, net returns and benefit: cost ratio of maize.